Design and Implementation of Probe Driver Teleoperative Force Feedback System - Amjad Ali Syed; Xing-guang Duan; Arbab Nighat Khizer; Mengli Mengli; Xiangzhan Kong; Qiang Huang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The basic need of neurosurgery is to insert the probe into the key hole linearly for performing functional neurosurgery, trigeminal neuralgia surgery, biopsies, deep brain stimulation, and stereo-EEG. Recently, tele-robotic systems have been introduced to assist surgeon during invasive procedures to obtain desired results. In this paper, a linear probe driving tele-operative system with force feedback is proposed. The proposed system is highly accurate, stable, and safe and provides haptic transparency to the surgeon during its operation. The master slave architecture, control system and software application are designed to inject and eject probe driving trials. The experiments are performed on a piecewise linear Plasticine model. The accuracy, stability, repeatability of the system and haptic force feedback fidelity are discussed in the results.  DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5277